Características e determinantes da primeira emissão de debêntures - Reis, Roberto João Ferreira Freitas Rodrigues dos (2008)
Debt financing decisions have impact in capital structure by altering the leverage, ownership structure and maturity of debt. Most popular theories about composition of debt predicts negative reaction of stocks when a firm issue public bonds. My results does not support that effect at least directly. However, the determinants of the issue are consistent with the predictions, with some particularities about Brazilian economy.